Age at school entry and intergenerational educational mobility - Philipp C. Bauer; Regina T. Riphahn (Institute for the Study of Labor (IZA), 2009)
We use Swiss data to test whether intergenerational educational mobility is affected by the age at which children first enter (primary) school. Early age at school entry significantly affects mobility and reduces the relative advantage of children of better educated parents.
urn:nbn:de:101:1-20090210168
Keywords: I2; I21; J24; D30; 330; Age at entry; intergenerational transmission of education; educational mobility; Schule; Altersgruppe; Bildungschancen; Generationenbeziehungen; Schweiz